Estudio de caso troncal bolivariana localidad 20 de Sumapaz (2019)
The locality 20 of Sumapaz has a road network of 120 km which crosses the National Natural Park of Sumapaz, an element that represents a public management problem since it puts to debate institutional interests, both nationally and locally and at different levels prioritize their missionary approaches by stopping the intervention on the road and as a consequence they affect the quality of life of peasants in terms of mobility, transportation of their products and access to institutional services concentrated in urban Bogotá.